Microscopic Characterization of GRP1 PH Domain Interaction with Anionic Membranes. Issue 6 (25th November 2019) - Pant, Shashank; Tajkhorshid, Emad
Abstract : The pleckstrin homology (PH) domain of general receptor for phosphoionositides 1 (GRP1‐PHD) binds specifically to phosphatidylinositol (3, 4, 5)‐triphosphate (PIP3 ), and acts as a second messenger. Using an extensive array of molecular dynamics (MD) simulations employing highly mobile membrane mimetic (HMMM) model as well as complementary full membrane simulations, we capture differentiable binding and dynamics of GRP1‐PHD in the presence of membranes containing PC, PS, and PIP3 lipids in varying compositions. While GRP1‐PHD forms only transient interactions with pure PC membranes, incorporation of anionic lipids resulted in stable membrane‐bound configurations. We report the first observation of two distinct PIP3 binding modes on GRP1‐PHD, involving PIP3 interactions at a "canonical" and at an "alternate" site, suggesting the possibility of simultaneous binding of multiple anionic lipids. The full membrane simulations confirmed the stability of the membrane bound pose of GRP1‐PHD as captured from our HMMM membrane binding simulations. By performing additional steered membrane unbinding simulations and calculating nonequilibrium work associated with the process, as well as metadynamics simulations, on the protein bound to full membranes, allowing for more quantitative examination of the binding strength of the GRP1‐PHD to the membrane, we demonstrate that along with the bound PIP3, surrounding anionic PS lipids increase the energetic cost of unbinding of GRP1‐PHD from the canonical mode, causing them to dissociate more slowly than the alternate mode. Our results demonstrate that concurrent binding of multiple anionic lipids by GRP1‐PHD contributes to its membrane affinity, which in turn control its signaling activity. © 2019 Wiley Periodicals, Inc. Abstract : Differential binding modes of GRP1‐PHD to anionic membranes captured from molecular dynamics simulations. Starting with the unbound GRP1‐PHD in solution (left), highly mobile membrane mimetic model was able to capture two distinct PIP3 ‐binding modes: Canonical mode (middle) and Alternate mode (right), suggesting the presence multiple membrane binding interfaces of GRP1‐PHD. Large number of PS lipids (shown in green) were observed to cluster around the membrane‐bound PHD, contributing toward its higher membrane binding affinity.